Techniques for Determining the Location and Layout of Tempe Production Businesses - Ansori, Hafid; Kharisma, Rozza (Journal of Economics, Bussiness and Management Issues, 2026)
The tempe industry is one of the micro, small, and medium enterprise (MSME) sectors that plays an important role in supporting national food security by providing affordable plant-based protein for the community. However, this industry faces several challenges, including fluctuations in soybean prices, increasing market competition, and the need to improve production efficiency. Therefore, optimizing production processes through proper location selection and effective business layout planning becomes an important aspect to ensure business sustainability. This study aims to analyze the importance of location selection techniques and business layout planning in improving production performance in the tempe industry. The research uses a qualitative approach through a literature review method by examining location theory, facility layout theory, and findings from relevant previous studies. The results indicate that selecting a strategic business location, particularly one that is close to raw material sources and target markets, can reduce transportation costs and improve distribution efficiency. In addition, a production layout designed based on workflow processes can minimize production bottlenecks, reduce operational waste, and create a safer and more organized working environment. The integration of strategic location selection and effective layout planning can significantly improve operational efficiency and strengthen the competitiveness of tempe MSMEs. Therefore, implementing appropriate location and layout strategies is essential to support the sustainability of tempe production businesses and enhance their contribution to local economic development and national food security.